Proses Penyidikan Terhadap Illegal Logging: Studi Kasus Polres Batanghari: Investigation Process for Illegal Logging: Batanghari Police Case Study - Ario Putra Astriyadi; Tri Imam Munandar (Asosiasi Pengajar Hukum Pidana dan Kriminologi Indonesia (ASPERHUPIKI), 2024)
The number of investigations into criminal illegal logging carried out by the Batanghari Police has increased from year to year. Therefore, the problem of illegal logging in Batanghari Regency must be immediately addressed as well as possible so as not to further damage the forests in Batanghari Regency. There is concern that if the forests in Batanghari Regency, which play a major role in supporting human life, are damaged by the actions of certain individuals, then natural disasters will be difficult to avoid. Apart from that, ecosystem life will be greatly disrupted and lives will also be affected. The aim of this investigation is to clarify the process of investigating trees without permits (illegal logging). This type of research carried out by the author is the result of a discussion investigation, the following conclusions can be drawn. Batanghari police investigators conducted an investigation into the criminal act of felling trees without a permit in Batanghari district, arrested the suspect, secured evidence, and interrogated him at the police office. TKP, Execution of additional files followed up, examination of suspects, examination of witnesses and TKP continued to the investigation level evidentiary process by Batanghari Police Detectives. The obstacles faced by Batanghari Police investigators in investigating the crime of felling trees without permission in Batanghari Regency include limited investigative resources, difficulty in reaching illegal logging locations, the escape of the perpetrators and the involvement of the community itself. and transporters, but also collectors and financiers when carrying out investigations.